Experimental study on mechanical behaviour of concrete beams with shredded plastics - De Jesus, Richard M. (Animo Repository, 2018)
In recent years, more attention is being paid to alternative disposal of wastes to lessen the harmful impact of these wastes to the environment. In the construction industry, alternative disposal of waste comes in the form of utilization of waste as a substitute construction material. Plastic, typically in the form of plastic bags and bottles, is one of the most abundant wastes in Manila, and, also among the most problematic when it comes to disposal due to its non-biodegradable nature. Hence, more attention is given to alternative use of plastics as a substitute material in construction. In this study, experimental investigation was conducted to assess the performance of concrete beams with shredded plastics, sourced out locally, as a supplementary material. Strength properties of a concrete beam, in terms of compression, tension, and flexure, were investigated for both plain concrete and concrete with shredded plastics. Results showed that concrete with shredded plastics were slightly higher than that of plain concrete in terms of tension and compression strength. Flexural strength of concrete with shredded plastic, also showed higher strength than that of plain concrete. Additionally, this study showed the applicability of elastic flexural theory to concrete beams with plastics. © Int. J. of GEOMATE.